Sustainable polyacetals from isohexides - Rajput, B. S.; Gaikwad, S. R.; Menon, Shamal K.; Chikkali, Samir H. (Green Chemistry, 2014)
A single step synthetic protocol to access a small family of renewable diacetals was established. The resultant chiral diacetals are valuable building blocks in pharmaceuticals and materials science. To demonstrate their synthetic competence, isohexide-diacetals (2a-c) were subjected to acetal metathesis polymerization and the corresponding polymers (poly2a-c) were isolated as white solids with molecular weights in the range 3200-27 600 (g mol(-1)). The semi-crystalline polymers displayed glass transition temperatures between 38-65 degrees C and melting temperatures in the range 103-156 degrees C. The isohexide derived polyacetats are stable under practical washing and rinsing conditions but degrade in slightly acidic media.

Synthesis of renewable copolyacetals with tunable degradation - Rajput, Bhausaheb S.; Chander, Umesh; Arole, Kailash; Stempfle, Florian; Menon, Shamal K.; Mecking, Stefan; Chikkali, Samir H. (Macromolecular Chemistry and Physics, 2016)
Acetal metathesis copolymerization (AMCP) of renewable isohexide diacetals and aliphatic long-chain diacetals is reported and access to a small family of copolyacetals has been established. Crucial 1-2D NMR and MALDI-ToF-MS findings unambiguously confirm the existence of a copolymeric structure. In a stark contrast to the earlier reported isohexide-polyacetals, the current copolyacetals reveal very slow degradation. Hydrolytic degradation of copolyacetal pellets is extremely slow at pH 7, whereas only 30% degradation over a period of 15 d is observed in 9 M hydrochloric acid solution. GPC investigations reveal that with increasing chain-length the rate of degradation reduces, whereas copolyacetals with short-chain aliphatic segments display a faster degradation profile. The reduced rate of degradation can be attributed to the hydrophobic nature of long-chain acetal segments. In situ NMR spectroscopy reveals the existence of formates, hemiacetals, and diols as degradation products. Thus, the rate of degradation can be tuned by the judicious choice of isohexide-diacetal and linear-diacetals in a copolyacetal.
Keywords: copolyacetals; degradable polymers; diacetals; isohexides; renewable polymers

Secondary interactions arrest the hemiaminal intermediate to invert the modus operandi of schiff base reaction: a route to benzoxazinones - Patel, Ketan; Deshmukh, Satej S.; Bodkhe, Dnyaneshwar; Mane, Manoj; Vanka, Kumar; Shinde, Dinesh; Rajamohanan, Pattuparambil R.; Nandi, Shyamapada; Vaidhyanathan, Ramanathan; Chikkali, Samir H. (Journal of Organic Chemistry, 2017)
Discovered by Hugo Schiff, condensation between amine and aldehyde represents one of the most ubiquitous reactions in chemistry. This classical reaction is widely used to manufacture pharmaceuticals and fine chemicals. However, the rapid and reversible formation of Schiff base prohibits formation of alternative products, of which benzoxazinones are an important class. Therefore, manipulating the reactivity of two partners to invert the course of this reaction is an elusive target. Presented here is a synthetic strategy that regulates the sequence of Schiff base reaction via weak secondary interactions. Guided by the computational models, reaction between 2,3,4,5,6-pentafluoro-benzaldehyde with 2-amino-6methylbenzoic acid revealed quantitative (99%) formation of 5-methyl-2-(perfluoropheny01,2-dihydro-4H-benzo[d][1,3]oxazin-4-one (15). Electron donating and electron withdrawing ortho-substituents on 2-aminobenzoic acid resulted in the production of benzoxazinones 936. The mode of action was tracked using low temperature NMR, IN vis spectroscopy, and isotopic (O-18) labeling experiments. These spectroscopic mechanistic investigations revealed that the hemiaminal intermediate is arrested by the hydrogen-bonding motif to yield benzoxazinone. Thus, the mechanistic investigations and DFT calculations categorically rule out the possibility of in situ imine formation followed by ring-closing, but support instead hydrogen-bond assisted ring-closing to prodrugs. This unprecedented reaction represents an interesting and competitive alternative to metal catalyzed and classical methods of preparing benzoxazinone.

Self-assembly of P-chiral supramolecular phosphines on rhodium and direct evidence for Rh-catalyst-substrate interactions - Koshti, Vijay S.; Sen, Anirban; Shinde, Dinesh; Chikkali, Samir H. (Dalton Transactions, 2017)
Supramolecular phosphine-derived catalysts are known to provide high enantioselectivity in asymmetric transformations such as hydrogenation, but direct evidence unravelling the role of secondary interactions is largely missing. As a representative case study, the role of hydrogen bonding in asymmetric hydrogenation catalysed by p-chiral supramolecular phosphines is investigated. To establish the nature of hydrogen bonding in the self-assembled Rh-complex, NMR experiments were performed at different concentrations and temperatures. It was found that with increasing concentration of 1-(3-(phenyl(o-tolyl)phosphanyl) phenyl) urea ligand (L1), the NH and NH2 peaks shift downfield. This indicated the presence of intermolecular hydrogen bonding in L1. This observation was further supported by variable temperature NMR experiments wherein, with decreasing temperature, the NH and NH2 resonances of L1 shifted downfield. The downfield shift once again suggests the existence of intermolecular hydrogen bonding in L1. In contrast, the chemical shift of NH and NH2 signals did not significantly change with increasing concentration of the self-assembled Rh-complex (C1). This observation suggested the existence of intramolecular hydrogen bonding in the self-assembled complex. The concentration experiment was further corroborated by variable temperature NMR experiments. No change in the chemical shift of NH2 resonance could be detected with decreasing temperature, which corroborates the existence of intramolecular hydrogen bonding in C1. In a stoichiometric experiment, C1 was treated with hydrogenation substrate N-acetyldehydrophenylalanine (S2) and the proton NMR was recorded. The NH2 protons of the selfassembled Rh-complex were found to shift downfield, as compared to untreated parent C1. These observations indicated that there is a hydrogen bonding interaction between the Rh-complex and the substrate. To further attest this hypothesis, NH and NH2 groups were exchanged with ND and ND2 groups, respectively, and a self-assembled Rh-complex was prepared using the deuterated supramolecular phosphine ligand L1.D. When the deuterated Rh-complex (C1.D) was treated with substrate S2, the ND and ND2 resonances were found to shift downfield. Thus, the labelling experiment further authenticated the existence of catalyst-substrate interactions. The presence of this catalyst-substrate interaction could be one of the parameters that leads to high enantiomeric excess in the asymmetric hydrogenation reaction of S2.

Synthesis of isohexide-di(ether-ene)s and ADMET polymerization - Rajput, Bhausaheb S.; Lekshmy, Kalpakasseril Girija; Menon, Shamal K.; Chikkali, Samir H. (Green Materials, 2017)
As the fossil fuel reserves deplete and the greenhouse gases increase, the scientific community is challenged to provide sustainable solutions. Sugar-based isohexides can be modified to prepare a library of isohexide-diene monomers for polymerization. Such isohexide diene monomers can be subjected to Acyclic Diene Metathesis Polymerization to obtain green materials. Here we report a single step synthetic protocol to access a small family of isohexide-di(ether-ene)s and the corresponding polymers. The isohexide di(ether-ene)s 2a-2c could be isolated in good to excellent yields under optimized conditions. The resultant isohexide-di(ether-ene)s 2a-2c are potential versatile building blocks for pharmaceuticals and material science. The synthetic utility of 2a-2c was demonstrated by subjecting them to ADMET polymerization using Grubbs 1st and 2nd generation catalysts. The resultant viscous material was evaluated using 1H NMR and MALDI-ToF-MS, which suggests the formation of anticipated ADMET polymers

Synthesis of meta-substituted monodentate phosphinite ligands and implication in hydroformylation - Deshmukh, Satej S.; Gaikwad, Shahaji R.; Pandey, Swechchha; Mali, Pramod S.; Chikkali, Samir H. (Journal of Chemical Sciences, 2017)
Synthesis of meta-substituted phosphinite ligands 3,3'-(methoxyphosphanediyl) bis(N, N-diethylaniline) (4a) and methoxybis(3-methoxyphenyl) phosphane (4b), in high yields, has been demonstrated. Typical phosphorus chemical shift between 110-120 ppm, appearance of methoxy protons and corresponding carbon, as well as ESI-MS spectra unambiguously confirmed the existence of phosphinite ligands 4a and 4b. To demonstrate the synthetic usefulness of 4a and 4b, these ligands were tested in the rhodium catalyzed hydroformylation of 1-octene. The diethylamine substituted ligand 4a was found to be highly active, whereas 4bwas less reactive but revealed slightly better regioselectivity of 62% under optimized conditions. Additionally, 4a and 4b were found to catalyze the hydroformylation of styrene, 1-undecenol and 1,1-disubstituted functional olefin, methyl methacrylate. Both the ligands displayed excellent conversion of styrene, and 4b revealed an excellent branch selectivity of 75%. Although 1-undecenol proved to be amenable to hydroformylation (85-90% conversion to aldehyde), both the ligands failed to discriminate between the linear and branched products. Substrate methyl methacrylate proved to be highly challenging and reduced conversion (between 33-42%) was observed under optimized conditions. Ligand 4a was found to be highly selective towards linear aldehyde (81% linear selectivity).

Solvent-free hydroxylation of unactivated C-H bonds in small molecules and macromolecules by a Fe complex - Chatterjee, Debasmita; Sajeevan, Amritha; Jana, Sandipan; Birajdar, Rajkumar S.; Chikkali, Samir H.; Sivaram, Swaminathan; Sen Gupta, Sayam (ACS CATALYSIS, 2024)
Keywords: Ball milling; solid-state C-H hydroxylation

Synthesis of imine-phenoxy ligated palladium complexes for norbornene homopolymerization - Birajdar, Rajkumar S.; Gupta, Poonam; Gonnade, Rajesh G.; Chikkali, Samir H. (Inorganic Chemistry, 2024)
Metal complexes with tunable ligands play a crucial role in olefin polymerization and impart control over molecular weight, crystallinity, and stereoregularity. We report the single-step synthesis of imine-phenoxy ligands in excellent yields (81-93%). The identity of electronically tuned imine-phenoxy ligands was unambiguously ascertained by using a combination of spectroscopic and analytical methods. These ligands were treated with [Pd(COD)MeCl] in the presence of 2,6-lutidine, resulting in the formation of discrete mononuclear palladium complexes Pd1-Pd4 in excellent yields. 1-2D NMR spectroscopy, mass spectrometry analysis, and single-crystal X-ray diffraction confirmed the identity of the palladium complexes. X-ray analysis revealed a distorted square planar geometry around the palladium center. Proton NMR analysis suggested that the Pd1 catalyst was deshielded, indicating electronically deficient palladium metal compared to the other complexes. Moreover, the Pd1 catalyst showed the highest buried volume percentage (%Vbur = 44.9). When exposed to norbornene, Pd1-Pd4 were found to be active and produced poly(norbornene) (PNB). High-temperature SEC analysis revealed that the electronically deficient and sterically hindered Pd1 catalyst produced the highest molecular weight polymer (PNB 37.4 kDa). Boron and aluminum-based cocatalysts were screened, and MMAO was found to outperform others with high catalytic activity (up to 63.2 x 105 g of PNB (mol Pd)-1 h-1).